Hubungan Antara Kualitas Pelayanan Dengan Kepuasan Pasien Puskesmas Pajang Laweyan Surakarta - Nila Indri Pamungkas Suwardi, Liliek Winarni (Solidaritas, 2018)
Research on the relationship between the quality of service to the satisfaction of the patient in clinic post Laweyan, surakarta aims to find out the relationship between the quality of service to the satisfaction of the patient. Methods used quantitative methods associative. The analysis used pearson product moment.The results of the analysis of the data shows the five dimensions of service quality have a positive correlation with patient satisfaction Clinics Post with correlation of Tangible (Physical Ketampakan) 0,556; Reability 0.665 (reliability); Responsiveness (Responsiveness) 0.520; Assurance (Assurance) 0.665; Emphaty (Attention) 0.665 significance level where p 0.000 < 0.05.Thus it can be concluded that is